Diffusion Bonding Material Tungsten-Baja dengan Interlayer Ag-4% Cu - Sirod Hantoro; Tiwan Tiwan (Teknoin, 2005)
The objective of this research is to study the implementation diffusion bonding process on tungsten and low carbon steel system with interlayer Ag-4% Cu, as well as investigate the influence of process parameters such as temperatur, initial pressure and heating time to the shear strength of the joint. Based on the result of shear test, initial pressure 48-144MPa has positive effect to the shear strength. Likewise by improving temperature of heating, it will improve the shear strength. The optimal shear strength is obtained at the temperature 9500C with maximal shear strength is 165 MPa and its bonding ratio 85%. The temperature 9500C and pressure of 144 MPa diffusion bonding has been successfully done with the heating time of 15 minute.Optical and stereomicroscopy on fracture surface after shear testing of the samples reveal tran granular fracture occur at the interlayer. Microstructure analysis at the interlayer reveals in variation microstructure as function of temperature, initial pressure, and heating time. The thickness of interlayer decrease with increasing the temperature, initial pressure and heating time. Other wise, the thickness of grain boundary and second phase area increase with the increasing the temperature, initial pressure and heating time. Based on the SEM/EDS examination, the element of Fe has the dominant distribution. There is accumulation of the element Fe on the limit area with tungsten. The distribution of the element of W, Ag and Fe increase with the increasing the heating time. Diffusivity of some atoms has been calculated based on SEM data at the interlayer. At 9500C, the diffusivity among the element of atom namely are D Ag to Fe= 0,00195 m2s-1, D Fe to Ag=0,02364 m2s-1, DAg to W=0,0061 m2s-1 , and DW to Ag= 0,025034 m2s-1.Keywords: Diffusion Bonding, material, Tungsten, steel, interlayer.